Systolic inversion algorithms for building cryptographic systems based on security measurement in IoT-based advanced manufacturing - Yi, Haibo (Measurement : journal of the International Measurement Confederation, 2020)
•Post-quantum security solution based on security measurement.•Systolic architecture of inversion for building post-quantum crypto-system.•Employing post-quantum crypto-system to IoT security measurement. Internet of Things (IoTs) have become one of the most popular techniques and widely used in advanced manufacturing and other engineering areas. As the applications of IoT-based advanced manufacturing rapidly increase, security measurement of data management has become one of the most crucial challenges in IoT-based advanced manufacturing. It is claimed that such systems are vulnerable to quantum computer attacks. Thus, it is very urgent to improve data management based on security measurement. In this paper, we improve multivariate cryptographic systems for IoT-based advanced manufacturing based on employing new inversion algorithms. Compared with related designs, the proposed design has better performance and meets the resource requirement of IoTs and the secure requirement of data management in advanced manufacturing, which is very suitable to build multivariate cryptographic systems for securing data management based on security measurement in IoT-based advanced manufacturing.